Predicting Well-Being Among the Elderly: The Role of Coping Strategies - Galiana, Laura; Tomás, José M.; Fernández, Irene; Oliver, Amparo (Frontiers in Psychology, 2020)
Objectives: This study aims to give a wider view on the role of coping strategies on elderly’s well-being, by means of literature-based competitive structural equation models (SEM). Methods: 857 older adults were surveyed with Ryff’s scales of Psychological Well-being and the Coping Strategies Questionnaire. Competitive full SEMs were tested. Results: The best fitting model was the one in which the religious coping dimension was removed, leaving the remaining dimensions defined by problem- and emotion-focused coping, which explained both psychological and subjective well-being factors (χ2(46)=165.910, p<.001; CFI=.906; GFI=.957; RMSEA=.058 [.048, .067]). Discussion: Results pointed the relevance of coping strategies for elderly achieving an adequate well-being, in its two dimensions, with emotion-focused coping strategies being the ones with the highest and negative predictive power over the two dimensions of well-being. Interventions aiming at improve old people’s well-being should, then, put their focus on the decrease of use of emotional coping strategies.